Analysis of the Effectiveness of the BSPS Program of the Ministry of PUPR in Pakkat District, Humbang Hasundutan Regency - Roy R Simanjuntak; Badaruddin Badaruddin; Tengku Irmayani (PERSPEKTIF, 2025)
This study aims to analyze the effectiveness of the Self-Help Housing Stimulant Assistance Program (BSPS) in Pakkat District, Humbang Hasundutan Regency, using a qualitative approach and a public policy evaluation framework from William N. Dunn. The results of the study indicate that this program is highly effective in enhancing the quality of housing for low-income communities, with active community participation and local 'gotong royong' practices (marsiadapari) playing a significant role. Efficiency is achieved through the optimization of regional resources, although logistical challenges remain an obstacle. The limited value of assistance is not entirely sufficient to meet development needs, but the spirit of self-help is the primary support. The distribution of aid is relatively even; however, data verification still needs improvement. The program's responsiveness to local culture is relatively good, although administrative and legal constraints hinder the accuracy of the target. Social capital and community participation have proven to play a crucial role in the successful implementation of the program. These findings emphasize the importance of participatory and contextual approaches in housing policy and recommend replicating similar strategies in other regions with similar social characteristics.